2009
DOI: 10.1016/j.ijid.2008.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between circulating vascular endothelial growth factor and its soluble receptors in adults with dengue virus infection: a case–control study

Abstract: The changes in VEGF and its soluble receptors highlight the importance of vascular permeability cytokines in the pathogenesis of DHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
3
21
1
Order By: Relevance
“…However, many studies have reported the relationship between VEGF and vascular leakage in severely infected dengue patients. [26][27][28] Our previous study reported the evidence of endothelial cells dysfunction/damage by demonstrating elevated soluble thrombomodulin in the febrile stage in DSS patients. 29 Moreover, in this study, we also found significant correlation between VEGF and EGF from day 0 to day +1.…”
Section: Discussionmentioning
confidence: 97%
“…However, many studies have reported the relationship between VEGF and vascular leakage in severely infected dengue patients. [26][27][28] Our previous study reported the evidence of endothelial cells dysfunction/damage by demonstrating elevated soluble thrombomodulin in the febrile stage in DSS patients. 29 Moreover, in this study, we also found significant correlation between VEGF and EGF from day 0 to day +1.…”
Section: Discussionmentioning
confidence: 97%
“…However, the discriminatory ability of sFlt-1 was suboptimal: a cut-off level of 16.9 ng/mL had a sensitivity of 52% and a specificity of 84% for the diagnosis of occult placental malaria. Finally, in patients with dengue virus infection, serum sFlt-1, but not VEGF, differentiated between patients with dengue fever and dengue hemorrhagic fever 97 . At a cut-off value of 350 pg/mL, sFlt-1 levels predicted dengue hemorrhagic fever with a sensitivity of 79% and a specificity of 78%.…”
Section: Mediators Of Vascular Tone and Permeability: Vegf And Sflt-1mentioning
confidence: 89%
“…One originality of this study is that, contrary to previous reports, soluble factors level were measured throughout the acute phase [14,18,21-23,49,50]. Chemokines are produced by activated monocytes and macrophages, which are known DENV target cells [51].…”
Section: Discussionmentioning
confidence: 99%